Yap/Taz transcriptional activity is essential for vascular regression via Ctgf expression and actin polymerization - Nagasawa-Masuda, Ayumi (PLoS One, 2017)
Vascular regression is essential to remove redundant vessels during the formation of an efficient vascular network that can transport oxygen and nutrient to every corner of the body. However, no mechanism is known to explain how major blood vessels regress during development. Here we use the dorsal part of the caudal vein plexus (dCVP) in Zebrafish to investigate the mechanism of regression and discover a new role of Yap/Taz in vascular regression. During regression, Yap/Taz is activated by blood circulation in the endothelial cells. This leads to induction of Ctgf and actin polymerization. Interference with Yap/Taz activation decreased Ctgf production, which decreased actin polymerization and vascular regression. These results implicate a novel role of Yap/Taz in vascular regression.